A major role for ferroptosis in Mycobacterium tuberculosis–induced cell death and tissue necrosis - Amaral, Eduardo P. (J Exp Med, 2019)
Necrotic cell death during Mycobacterium tuberculosis (Mtb) infection is considered host detrimental since it facilitates mycobacterial spread. Ferroptosis is a type of regulated necrosis induced by accumulation of free iron and toxic lipid peroxides. We observed that Mtb-induced macrophage necrosis is associated with reduced levels of glutathione and glutathione peroxidase-4 (Gpx4), along with increased free iron, mitochondrial superoxide, and lipid peroxidation, all of which are important hallmarks of ferroptosis. Moreover, necrotic cell death in Mtb-infected macrophage cultures was suppressed by ferrostatin-1 (Fer-1), a well-characterized ferroptosis inhibitor, as well as by iron chelation. Additional experiments in vivo revealed that pulmonary necrosis in acutely infected mice is associated with reduced Gpx4 expression as well as increased lipid peroxidation and is likewise suppressed by Fer-1 treatment. Importantly, Fer-1–treated infected animals also exhibited marked reductions in bacterial load. Together, these findings implicate ferroptosis as a major mechanism of necrosis in Mtb infection and as a target for host-directed therapy of tuberculosis.